Why chemical reactions happen - Keeler, James; Wothers, Peter; Oxford University Press (Oxford : Oxford University Press, 2003)
"Why Chemical Reactions Happen is written for students who are in their first year of a university chemistry course, or are about to embark on such a course. To understand how chemical reactions happen we need to know about the bonding in molecules, how molecules interact, what determines whether an interaction is favourable or not, and what the outcome will be. Answering these questions requires an understanding of topics from quantum mechanics, through thermodynamics, to 'curly arrows.' In this book all of these topics are presented in a coherent and co-ordinated fashion, showing how each leads to a deeper understanding of chemical reactions."--BOOK JACKET.
What makes a reaction go? -- Ionic interactions -- Electrons in atoms -- Electrons in simple molecules -- Electrons in larger molecules -- Reactions -- Equilibrium -- Rates of reaction -- Bonding in extended systems --conjugation t
Includes index.
Keywords: Chemical reactions